2022
DOI: 10.1021/acs.est.1c08631
|View full text |Cite
|
Sign up to set email alerts
|

Internal Dynamics and Metabolism of Mercury in Biota: A Review of Insights from Mercury Stable Isotopes

Abstract: Monitoring mercury (Hg) levels in biota is considered an important objective for the effectiveness evaluation of the Minamata Convention. While many studies have characterized Hg levels in organisms at multiple spatiotemporal scales, concentration analyses alone often cannot provide sufficient information on the Hg exposure sources and internal processes occurring within biota. Here, we review the decadal scientific progress of using Hg isotopes to understand internal processes that modify the speciation, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 158 publications
(541 reference statements)
0
28
0
Order By: Relevance
“…The determination of pharmaceutics and biocides in biota, including the analysis of invertebrates, plankton, fish, human tissues and fluids, birds, and marine mammals, is importance for assessing the risk for human health and environmental damage [ 38 , 39 ], as well as determining the potential ecological risk index [ 38 , 39 , 40 ]. The biomonitoring includes saltwater and freshwater mussels [ 1 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The determination of pharmaceutics and biocides in biota, including the analysis of invertebrates, plankton, fish, human tissues and fluids, birds, and marine mammals, is importance for assessing the risk for human health and environmental damage [ 38 , 39 ], as well as determining the potential ecological risk index [ 38 , 39 , 40 ]. The biomonitoring includes saltwater and freshwater mussels [ 1 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on coastal benthic invertebrates revealed similar Δ 199 Hg values (0.11 ± 0.06‰ for bivalve, 0.18 ± 0.11‰ for shrimp, 0.20 ± 0.14‰ for cephalopod, 0.21 ± 0.07‰ for gastropod, and 0.25 ± 0.07‰ for crab) but significantly lower δ 202 Hg values (−2.05 to −1.49‰, group-specific mean values) . Increases of both δ 202 Hg and Δ 199 Hg are seen from coastal/estuarine fishes , to open marine fishes and then to mammals/birds. As compared to their nearby sulfides, δ 202 Hg and Δ 199 Hg in our hydrothermal biota are slightly shifted by 0.19–0.51‰ (site-specific means: Longqi: 0.19 ± 0.42‰, P = 0.28; Duanqiao: 0.23 ± 0.62‰, P = 0.44; Kairei/Edmond: 0.51 ± 0.53‰, P = 0.08) and 0.04–0.14‰ (site-specific means: Longqi: 0.14 ± 0.17‰, P = 0.07; Duanqiao: 0.06 ± 0.11‰, P = 0.22; Kairei/Edmond: 0.04 ± 0.07‰, P = 0.43), respectively. These positive shifts of δ 202 Hg and Δ 199 Hg could be caused by bioaccumulation and trophic transfer of MMHg. However, the lack of significant correlations of MMHg% with δ 202 Hg and Δ 199 Hg (Figure S3) excludes this possibility.…”
Section: Resultsmentioning
confidence: 61%
“…We suspect that changes observed in our experiment are primarily due to inadvertent fatty acid extraction, which is supported by the positive association between the initial C:N ratio (a surrogate for lipid content) and the Hg gains made following preservation (Figures S3–S5). MeHg also preferentially binds to sulfur and selenium moieties in biological tissue, , which are uncommon in amino acids and fatty acids, further supporting this hypothesis.…”
Section: Resultsmentioning
confidence: 99%